ENHANCING KINDERGARTEN TEACHERS' COMPETENCE IN DEVELOPING INNOVATIVE LEARNING MEDIA BASED ON CANVA - Novitasari, Nurul; Anisah, Zulfatun (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study aims to understand how the Canva application can be beneficial for innovative learning for kindergarten teachers in Singgahan District. The method used in this research is qualitative. The study also aims to help kindergarten teachers in Singgahan District create a more enjoyable learning environment for students, as the quality of education heavily depends on the quality of teachers and the educational media used. One way to create a more engaging learning environment is by using the Canva application. Innovative learning becomes a tool for teachers to create educational materials using technology, making it easier for students to grasp the material provided and enhance their understanding during the learning process. The Canva application can be developed in the process of producing educational media, thus the goal of this study is to enhance innovative learning by using Canva as a teaching medium that fits the learning environment. Today's learning demands teachers to adapt to technology. Based on the findings of this research, learning using the Canva application is expected to assist educators in delivering innovative lessons, as Canva facilitates teachers in presenting material.